A cross-sectional study on knowledge, attitude, and behavior related to antibiotic use among undergraduate medical students in a tertiary care medical college, Kashmir - Mir, Shakeel Ahmad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antibiotics represent one of the most prescribed drugs worldwide. The overuse and misuse of antibiotics are key factors contributing to antibiotic resistance. It is estimated that more than 50% of antibiotics are purchased without a proper prescription. Self-medication with antibiotics has been identified as one form of irrational use contributing to increased morbidity and mortality. Antibiotic self-medication assumes a special significance among medical students as they are the future medical practitioners. The objective of this study was to assess the frequency of antibiotic self-medication among medical students and their knowledge and perception about antibiotic use and its dangers. Methods: Pre-validated questionnaires were distributed among 300 medical students by simple randomization out of which 246 were returned completely filled. The analysis was done by manual calculators, VassarStats, and SPSS. Results are expressed in frequencies and percentages. Results: The prevalence of antibiotic self-medication among medical students was found as high as 80.89%. It was also observed that the gender of the respondents did not influence significantly the practice of antibiotic self-medication. The majority (52.26%) of the respondents used penicillins, mostly for upper respiratory tract infections (88.94%). The major source of antibiotics was medical stores (87.93%). Most of the respondents (57.58%) stopped the antibiotics after symptoms disappeared. It was found that the student’s knowledge improved as they progressed in their study. However, the senior students scored poorly on the behavior/practice toward the use of antibiotics. Conclusions: There is an urgent need to improve education on antibiotic use in medical curricula. Furthermore, strict policies must be enforced to regulate dispensing of antibiotics.